Effects of vitamin D3 supplementation on serum 25(OH)D concentration and strength in athletes: a systematic review and meta-analysis of randomized controlled trials - Han, Q.; Li, X.; Tan, Q.; Shao, J.; Yi, M. (Journal of the International Society of Sports Nutrition, 2019)
Background: The purpose of this systematic review and meta-analysis is to investigate the effects of vitamin D3 supplementation on skeletal muscle strength in athletes. Vitamin D3 supplements or vitamin D3 fortified foods always have claims for bringing people health benefits including bone and muscle health. An up-to-date rigorous systematic review and meta-analysis is important to better understand the effect of vitamin D3 supplementation on muscle strength. Methods: English written randomized controlled trials (RCTs) that looked at effects of vitamin D3 supplementation on muscle strength in healthy athletes were searched using three databases (PubMed, Embase and Cochrane Library). Serum 25(OH)D above 30?ng/mL is considered to be sufficient in this systematic review and meta-analysis. Results: Five RCTs with 163 athletes (vitamin D3 n?=?86, placebo n?=?77) met inclusion criteria. Fourteen athletes were lost to follow-up and 149 athletes (vitamin D3 n?=?80, placebo n?=?69) were documented with complete result. Among athletes with baseline serum 25(OH)D values suggesting insufficiency, vitamin D3 daily dosage at 5000?IU for over 4?weeks led to a serum 25(OH)D concentration of 31.7?ng/mL. Athletes with sufficient serum 25(OH)D level at baseline were recruited in only one study, and the participants of which were assigned to either vitamin D3 at a daily dosage of 3570?IU or placebo for 12?weeks, their serum 25(OH)D sufficiency (VD: 37.2 ± 7.6 vs. 45.6 ± 7.6; PL: 38 ± 6.8 vs. 32 ± 8.4) was well maintained above the cut-off boundary. One repetition maximum Bench Press (1-RM BP) was not improved significantly (SMD 0.07, 95% CI: - 0.32 to 0.47, P = 0.72) and there was no significant increase in maximal quadriceps contraction (SMD -2.14, 95% CI: - 4.87 to 0.59, P = 0.12). Furthermore, there was no significant overall effect of vitamin D3 intervention on muscle strength in this meta-analysis (SMD -0.75, 95% CI: - 1.82 to 0.32, P = 0.17). Conclusion: Although, serum 25(OH)D concentrations after supplementation reached sufficiency was observed, muscle strength did not significantly improve at this point of current meta-analysis. Additional well-designed RCTs with large number of participants examined for the effect of vitamin D3 supplementation on serum 25(OH)D concentrations, muscle strength in a variety of sports, latitudes and diverse multicultural populations are needed.